New Zealand postgraduate medical training by distance for Pacific Island country-based general practitioners: a qualitative study - Rosalina Richards; Rory Miller; Kiki Maoate; Mark Smith; Allamanda Faatoese; Katharina Blattner (CSIRO Publishing, 2022)
IntroductionNew Zealand health training institutions have an important role in supporting health workforce training programmes in the Pacific Region. AimTo explore the experience of Pacific Island country-based doctors from the Cook Islands, Niue, and Samoa, studying in New Zealand's University of Otago distance-taught Rural Postgraduate programme. MethodsDocument analysis (16 documents) was undertaken. Eight semi-structured interviews were conducted with Pacific Island country-based students. Thematic analysis of the interviews was undertaken using the framework method. The two data sources were analysed separately, followed by a process to converge and corroborate findings. ResultsFor Pacific Island countries with no previous option for formal general practice training, access to a recognised academic programme represented a milestone. Immediate clinical relevance and applicability of a generalist medical curriculum with rural remote emphasis, delivered mainly at a distance, was identified as a major strength. Although technologies posed some issues, these were generally easily solved. The main challenges identified related to the provision of academic and other support. Traditional university support services and resources were campus focused and not always easily accessed by this group of students who cross educational pedagogies, health systems and national borders to study in a New Zealand programme. Study for individuals worked best when it was part of a recognised and supported Pacific in-country training pathway. DiscussionThe University of Otago's Rural Postgraduate programme is accessible, relevant and achievable for Pacific Island country-based doctors. The programme offers a partial solution for training in general practice for the Pacific region. Student experience could be improved by tailoring and strengthening support services and ensuring their effective delivery.